2023
DOI: 10.3390/jcs7070264
|View full text |Cite
|
Sign up to set email alerts
|

The Field-Effect Transistor Based on a Polyyne–Polyene Structure Obtained via PVDC Dehydrochlorination

Abstract: We report on the formation of the field-effect transistor based on a polyyne–polyene structure. Polyvinylidene chloride (PVDC) drop casting and its subsequent dehydrochlorination in KOH solution allowed for the formation of porous polyyne–polyene material, which was analyzed via transmission electron microscopy, Fourier-transform infrared spectroscopy, and Raman spectroscopy, revealing the presence of sp- and sp2-hybridized chained fragments in the structure. The polyyne–polyene-based field-effect transistor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…The D" band was previously related to the amorphization of carbon material [49,50]. This feature may also contain contributions from the C=C vibrations of polyenes [51,52]. The broad band in the frequency region of 1220-1270 cm -1 (similar to our D* band) in the Raman spectra of nanoporous activated carbon material was previously assigned to the amorphous carbonrelated D band and C-C vibrations of cis-polyacetelyne groups [50].…”
Section: Awc Ahtcsupporting
confidence: 64%
“…The D" band was previously related to the amorphization of carbon material [49,50]. This feature may also contain contributions from the C=C vibrations of polyenes [51,52]. The broad band in the frequency region of 1220-1270 cm -1 (similar to our D* band) in the Raman spectra of nanoporous activated carbon material was previously assigned to the amorphous carbonrelated D band and C-C vibrations of cis-polyacetelyne groups [50].…”
Section: Awc Ahtcsupporting
confidence: 64%
“…Such notation indicates that the obtained material has a chain-like structure, which is comprised from both sp-(polyynic) and sp 2 -hybridized (polyenic) linear fragments. In our previous studies, such structures were confirmed as a result of the dehydrohalogenation of PVDC [8] and PVDF [3]. Sp-containing materials are of recent interest, as theoretical studies reveal a tunable bandgap of such materials depending on the length of the carbon chain [9], their prominent thermal conductivity and mechanical strength [10].…”
Section: Introductionmentioning
confidence: 71%
“…The The spectrum of dh-PVDC (red line in Figure 3) shows relatively wide lines at 1160, 1560 and 2170 cm −1 . These lines are related to the vibrations of the C-C and of trans-isomeric polyenic structures [21], C=C of various carbon-based materials including disordered carbon and polyenes [8], and the vibrations of C≡C bonds [22][23][24], respectively. The plateau at 1210-1460 cm −1 is mainly attributed to the contribution of the D-line related to the breathing mode of sp 2 -hybridized clusters [25].…”
Section: Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…For more than 60 years, chemists have approached the study of carbyne by preparing monodisperse conjugated polyynes of ever-increasing lengths. Many of these efforts have sought to define asymptotic limits for physical properties capable of providing insight into the macromolecule. In addition, there is the purely synthetic challenge of the length of an sp carbon chain that can be accessed.…”
Section: Introductionmentioning
confidence: 99%